Self-Harm, Suicidal Ideation, and Suicide Attempts in Chinese Adolescents Involved in Different Sub-types of Bullying: A Cross-Sectional Study - Peng, Chang; Hu, Wenzhu; Yuan, Shanshan; Xiang, Jingjing; Kang, Chun; Wang, Mengni; Rong, Fajuan; Huang, Yunxiang; Yu, Yizhen (Frontiers in Psychiatry, 2020)
Background: Bullying tends to peak during adolescence and it is an important risk factor of self-harm and suicide. However, research on the specific effect of different sub-types of bullying is limited. Objective: The purpose of this study is to examine the associations between four common forms of bullying (verbal, physical, relational, and cyber) and self-harm, suicidal ideation (SI) and suicide attempts (SA). Method: This was a cross-sectional study of a sample including 4,241 Chinese students (55.8% boys) aged 11 to 18 years. Bullying involvement, self-harm, SI and SA were measured via The Juvenile Campus Violence Questionnaire (JCVQ). The association was examined through Multinomial logistic regression analysis, adjusted for demographic characteristics and psychological distress. Results: Bullying victimization and perpetration were reported by 18.0% and 10.7% of participants. The prevalence of self-harm, SI and SA were 11.8%, 11.8% and 7.1%, respectively. Relational bullying victimization and perpetration were significantly associated with SI only, SI plus self-harm, and SA. Physical bullying victimization and perpetration were risk factors of self-harm only and SA. Verbal victimization was significantly associated with SI only. Cyber perpetration was a risk factor of SA. Conclusions: The findings highlight the different effects of sub-types of bullying on self-harm and suicidal risk. Anti-bullying intervention and suicide prevention efforts should be prior to adolescents who are involved in physical and relational bullying.